Thoracic surgery for posttubercular hydropneumothorax in patient with cerebral palsy: a case report - Ankit Maheshwari; Ranjit Pawar; Ashish Dolas; Anurag Garg (Egyptian Journal of Chest Disease and Tuberculosis, 2024)
Cerebral palsy, a disorder presenting with various neurological and muscular manifestations depending on severity of cerebral involvement causes variable functional limitation. This presents as a challenge when major surgeries are planned. Thoracic surgeries need detailed evaluation and optimization due to functional limitations to attain optimal outcome. We report a case of cerebral palsy who underwent thoracic surgery for posttubercular hydropneumothorax.